Celiac disease in children with Type 1 Diabetes: impact of gluten freediet on diabetes management - Sponzilli, I.; Chiari, G.; Iovane, B. (Acta Biomedica Atenei Parmensis, 2011)
Background and aim of the work: the coexistence of Type 1 Diabetes (T1D) and celiac disease (CD) has been long established. Methods: Between January 2000 and December  2009, biopsy-proven CD was diagnosed in 12 children with T1D, giving a prevalence of 4.8 % in our out-patient clinic population. For each patient with coexisting T1D and CD, two control subjects with T1D and without CD who matched for age, sex and duration of diabetes were chosen. Prospective study follow up  lasted 24 months. At the enrolment time, and at 2-month intervals, time from diagnosis of T1D to diagnosis of CD, presence of gastrointestinal symptoms, HbA1c value, body mass index (BMI), Height and Weight SDS were collected by a single observer. Daily insulin requirements were also retained. Results: In 3 children, CD predated the onset of T1D and these children were excluded from the analysis. The 9 children who subsequently developed CD became earlier diabetic than control group (p=0.002). Eight of these children had CD diagnosis within 1 year after T1D onset. Seven out of 9 children were positive for TTG antibodies and all were positive for EMA. A significant increase in insulin requirement was found in CD children after 1 year of GFD (p= 0.02). The mean HbA1c value in CD children was higher than in the control subjects (p< 0.01).A significant increase in the insulin requirement after 1 year in the GFD compliant children was found. There was a significant improvement in height-SDS after institution of GFD  in the GFD-compliant children. Families of children with both T1D and CD reported higher burden than those affected by  T1D only (p= 0.001). The health care providers perceived family burden to increase with CD appearance (p< 0.05). Conclusion: Our study supports the importance of screening for CD in children with T1D 1. The early treatment with GFD of biopsy-confirmed CD children promotes a significant catch-up growth and prevents a growth failure during the follow-up.